INFECTION BY LEISHMANIA SPP. IN THE HAMSTER MESOCRICETUS AURATUS USING PROMASTIGOTES CULTURED IN VITRO - Rojas-Jaimes, Jesús Eduardo (2015)
Leishmaniasis is an endemic chronic degenerative disease of the mountains and jungle of Peru causing a social stigma in people who suffer from the wounds it causes. In vivo models make it necessary to study this neglected disease. In the present study immunosuppressed hamsters Mesocricetus auratus were infected with promastigotes of L. infantum, L. brazilensis, L. guyanensis and L. peruviana cultivated in vitro in order to observe the progression of the disease in four months. No disease progression was observed in the time stipulated probably by loss of virulence of the Leishmania sp. promastigotes used in the challenge. The results show that infection and progression of leishmaniasis requires conditions such as virulence and viability and that this is lost due to the passages in vitro cultures.